Pengaruh Latihan Plyometric terhadap Kemampuan Lompat Jauh Gaya Jongkok di Kelas X SMA Negeri 1 Tiganderket - Aldi Jamestra Ari Winata Purba; Aser Paul Nainggolan; Julius Boy Nesra Basgimata Barus (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study was motivated by the low performance of squat-style long jump among tenth-grade students of SMA Negeri 1 Tiganderket, which was suspected to be caused by insufficient leg muscle explosive power. Explosive leg muscle power is one of the most important physical components supporting long jump performance, especially during the take-off phase. Therefore, an effective training method is needed to improve this ability. This study aimed to analyze the effect of plyometric training on squat-style long jump performance among tenth-grade students of SMA Negeri 1 Tiganderket. The research employed a quantitative experimental method using a One Group Pretest-Posttest Design. The sample consisted of 36 students selected through purposive sampling techniques. The research instrument was a validated and reliable squat-style long jump test. Data were analyzed using a t-test after fulfilling the prerequisite tests of normality using the Shapiro-Wilk test and homogeneity testing. The results showed a significant improvement in squat-style long jump performance after the implementation of plyometric training. The average posttest score was higher than the average pretest score. Based on these findings, it can be concluded that plyometric training is effective in improving leg muscle explosive power, movement coordination, and squat-style long jump performance among students.